2021
DOI: 10.1002/uog.23100
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of contingent screening for placenta accreta spectrum disorders based on persistent low‐lying placenta and previous uterine surgery

Abstract: What are the novel findings of this work? Routine contingent screening for placenta accreta spectrum disorders based on the finding of placenta previa and previous uterine surgery is effective in a public healthcare setting. What are the clinical implications of this work? A contingent screening strategy for placenta accreta spectrum disorders is feasible in an ultrasound service where placenta localization is routinely performed. When linked to a placenta accreta diagnostic and surgical management service, ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 46 publications
1
16
2
1
Order By: Relevance
“…The predictive performance is similar to that reported in prospective studies with larger cohorts [26][27][28]. More recently, Countinho et al [29] described a screening protocol similar to that used in the present study, with a similar performance to that here reported. The previous studies were prospective and mostly conducted in university tertiary hospitals under research protocols.…”
Section: Discussionsupporting
confidence: 89%
“…The predictive performance is similar to that reported in prospective studies with larger cohorts [26][27][28]. More recently, Countinho et al [29] described a screening protocol similar to that used in the present study, with a similar performance to that here reported. The previous studies were prospective and mostly conducted in university tertiary hospitals under research protocols.…”
Section: Discussionsupporting
confidence: 89%
“…Advanced maternal age (age greater than 35 years old), multiparity, smoking, history of curettage, assisted reproductive technology, prior cesarean section, and prior placenta previa may increase the incidence of placenta previa [13][14][15] . The common complications of placenta previa include placenta accrete spectrum (PAS), uncontrolled antepartum/postpartum hemorrhage, so blood transfusion, hysterectomy, ICU care may need [16,17] .…”
Section: Discussionmentioning
confidence: 99%
“…Although early diagnosis of PAS is desirable to avoid associated adverse outcome [8][9][10][11][12][13][14][15] , it is challenging, and the diagnosis is often missed even in high-risk populations 16 . Among women with anterior placenta previa and previous CS, 1 in 3 is at risk of PAS 17 . Hence, the pretest probability of PAS is high in these women, and they should ideally be screened in early pregnancy.…”
Section: Introductionmentioning
confidence: 99%